Impact of pool design on spider and dytiscid recolonization patterns in a restored fen. Issue 5 (12th May 2021) - Drapeau Picard, André‐Philippe; Mazerolle, Marc J.; Larrivée, Maxim; Rochefort, Line
Abstract : Peatland pools present unique fauna and flora and contribute significantly to peatland biodiversity. The ecological functionality of artificial pools in restored peatlands is poorly documented. In this study, we investigated arthropod assemblages of 21 artificial pools in a restored fen in southeastern Canada and 16 pools from four pristine fens as reference ecosystems. Three years following restoration, predacious diving beetles (Coleoptera: Dytiscidae) and spiders (Araneae) were sampled within and around pools using minnow traps and pitfall traps, respectively. We used Bayesian community occupancy models to document arthropod recolonization. Twenty‐one dytiscid species were captured in pools. Dytiscid species richness was higher in artificial pools than in reference pools. Three dytiscid species were more likely to occur in deeper pools. Dytiscid species composition in artificial pools differed from reference pools. Seventy‐seven spider species were captured around pools. Spider species richness was higher around artificial pools than around reference pools. Seventeen spider species responded to vegetation cover, either positively or negatively. In contrast, spider species composition was similar between artificial and reference pools. We conclude that artificial pools should be along a gradient of pool depth, but also that fast‐growing vegetation should be introduced on pool margins to foster a quicker return of arthropod assemblages similar to reference ecosystems.